Multi-layer electrode preparation method

Through the multi-layer electrode preparation method, carbon nanotube-copper sulfide composite material is used as the positive electrode active material, and pore-forming agent is added to the electrode layer to form a porous structure, which solves the poor cycle stability, fast capacity attenuation and charge and discharge of lithium-ion batteries. The problem of low efficiency significantly improves the battery's cycle performance and fast charging performance.

CN119480921APending Publication Date: 2025-02-18GUOKE ENERGY TECH INNOVATION CENT (HEFEI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411588080.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have problems such as poor cycle stability, fast capacity attenuation and low charge and discharge efficiency.

Method used

By using a multi-layer electrode preparation method, a first slurry is formed by mixing the active material, a conductive agent and a binder, and adding a pore-forming agent therein to form a second slurry, alternately coated and dried to form at least one A multi-layer electrode structure of a first electrode layer and a second electrode layer. Among them, the positive electrode active material is a carbon nanotube-copper sulfide composite material, and the second electrode layer is a porous structure.

Benefits of technology

It significantly improves the cycle stability and electrochemical lithium storage performance of lithium-ion batteries, reduces irreversible capacity loss, improves charging and discharging efficiency, and improves the fast charging performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a multilayer electrode preparation method, and relates to the technical field of battery electrode production. The preparation method comprises the following steps: mixing an active material, a conductive agent and a binder to obtain first slurry; adding a pore-forming agent into the first slurry, and mixing to obtain second slurry; coating a current collector with the first slurry to form a first electrode layer; coating the first electrode layer with second slurry to form a second electrode layer; alternately coating and drying the first slurry and the second slurry to form a multi-layer electrode; wherein the multi-layer electrode at least comprises a first electrode layer and a second electrode layer, the active material is a positive electrode active material or a negative electrode active material, the positive electrode active material is a carbon nanotube-copper sulfide composite material, and the second electrode layer is of a porous structure. According to the preparation method of the multi-layer electrode provided by the invention, the lithium ion battery with good cycle performance, slow capacity fading and high charge-discharge efficiency can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery electrode production, and in particular to a method for preparing a multilayer electrode. Background Art

[0002] At present, lithium-ion batteries have developed to a very mature stage, but as the application scope of lithium-ion batteries continues to expand, people have put forward higher and higher requirements for the energy density of lithium-ion batteries. The cathode materials of lithium-ion batteries currently used mainly include lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, etc., which have low theoretical specific capacity and cannot meet the requirements for high energy density of lithium-ion batteries.

[0003] As semiconductor materials, transition metal sulfides have excellent performance in optics, electricity, and magnetic properties, and because their theoretical specific capacity is generally better than that of lithium cobalt oxide, they have attracted extensive research. However, copper sulfide, as a positive electrode material for lithium-ion batteries, also has the disadvantages of dissolution of intermediate polysulfides and its own volume expansion during charge and discharge cycles, resulting in rapid capacity decay and poor cycle reversibility in the battery. In addition to the characteristics of the material itself, the structure of the pole piece has a great influence on the fast charging performance. The double-layer coating technology can make the side away from the pole piece current collector have a higher porosity through different particle size gradients, achieve a larger liquid retention and increase the migration rate of lithium ions in the electrode. However, raw materials with larger particle sizes will inevitably reduce the fast charging performance of the material itself, thereby affecting the fast charging performance of the battery. Therefore, it is of great significance to develop lithium-ion batteries with good cycle stability, slow capacity decay, and high charge and discharge efficiency. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a multilayer electrode to solve the following technical problems: Lithium-ion batteries obtained by existing electrode preparation methods have problems such as poor cycle stability, rapid capacity decay, and low charge and discharge efficiency.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a multilayer electrode comprises at least the following steps: Mixing the active material, the conductive agent and the binder to obtain a first slurry; Adding a pore-forming agent into the first slurry and mixing the mixture to obtain a second slurry; Applying the first slurry on the current collector to form a first electrode layer; coating the second slurry on the first electrode layer to form a second electrode layer; The first slurry and the second slurry are alternately coated and dried to form a multilayer electrode; Wherein, the multilayer electrode includes at least one first electrode layer and one second electrode layer, the active material is a positive electrode active material or a negative electrode active material, the positive electrode active material is a carbon nanotube-copper sulfide composite material, and the second electrode layer is a porous structure.

[0006] As a further solution of the present invention: the porosity of the second electrode layer far away from the current collector is greater than the porosity of the second electrode layer close to the current collector.

[0007] As a further embodiment of the present invention, the preparation of the positive electrode active material comprises at least the following steps: Add ethyl cellulose to titanium isopropoxide and terpineol and stir until completely dissolved, then place in an agate mortar; Then, copper sulfide nanoparticles and hydroxyl multi-walled carbon nanotubes are added and fully ground until no obvious particles are present to obtain a positive electrode active material; Wherein, the mass ratio of the hydroxyl multi-walled carbon nanotubes to the nano copper sulfide is 1:2-4.

[0008] As a further solution of the present invention: the method for preparing the copper sulfide nanoparticles comprises at least the following steps: copper sulfate pentahydrate and polyvinyl pyrrolidone are added into water and dissolved to obtain solution A; Dissolve sodium thiosulfate pentahydrate in water to obtain solution B; The solution A and the solution B are mixed evenly and then transferred into a reaction kettle and sealed, reacted at 160-180°C for 4-6 hours, cooled to room temperature, washed and centrifuged, and placed in an oven for drying to obtain copper sulfide nanoparticles; Wherein, the particle size of the copper sulfide nanoparticles is 150-500nm.

[0009] As a further solution of the present invention: the pore-forming agent is ammonium bicarbonate, and the added amount of the pore-forming agent accounts for 0.1-5% of the mass of the second slurry.

[0010] As a further solution of the present invention: the preparation temperature of the second slurry is less than or equal to 30°C, and the drying temperature is greater than or equal to 70°C.

[0011] As a further solution of the present invention: the surface density of the first slurry accounts for 20% to 80% of the overall surface density, the surface density of the second slurry accounts for 20% to 80% of the overall surface density, and the sum of the first slurry and the second slurry is the overall surface density.

[0012] As a further solution of the present invention: the thickness of the first electrode layer is at least 12 μm, the thickness of the second electrode layer is at least 10 μm, and the thickness of the multiple layers of the first electrode layer and the multiple layers of the second electrode layer is 300-500 μm.

[0013] As a further embodiment of the present invention: the negative electrode active material includes at least one of natural graphite or artificial graphite, the conductive agent includes at least one of self-conductive carbon black, acetylene black, carbon nanotubes or graphene, and the binder includes at least one of ethyl cellulose, titanium isopropoxide, terpineol, polyvinylidene fluoride, hexafluoropropylene, hydrogenated nitrile rubber or styrene butadiene rubber. Beneficial effects of the present invention: (1) The present application selects a carbon nanotube-copper sulfide composite material as a positive electrode active material, so that the lithium-ion battery has good cycle stability and electrochemical lithium storage performance. The first slurry and the second slurry are alternately coated on the pole piece of the lithium-ion battery to form a multilayer electrode structure, which stabilizes the electrode structure on the one hand, and inhibits the "shuttle effect" unique to lithium-ion batteries on the other hand, which can reduce the irreversible capacity loss during the cycle of lithium-ion batteries, significantly improve the charge and discharge efficiency, and greatly improve the cycle performance of lithium-ion batteries. Specifically, during the preparation of the carbon nanotube-copper sulfide composite material, the copper sulfide nanoparticles are uniformly dispersed in the hydroxyl multi-walled carbon nanotubes, wherein the hydroxyl multi-walled carbon nanotubes effectively inhibit the dissolution of the reaction intermediate polysulfide, which not only improves the conductivity of the composite material, but also provides a transmission path for the migration of Li+, which is conducive to the contact between Li+ and the active substance copper sulfide nanoparticles, making the reaction easy to occur, so that the obtained lithium-ion battery has good electrochemical lithium storage performance; on the other hand, the hydroxyl multi-walled carbon nanotubes also enhance the stability of the composite material structure to a certain extent, so that the reversibility of the composite material in the electrochemical cycle is improved.

[0014] (2) In the present application, a pore-forming agent, ammonium bicarbonate, is added to the second slurry to form upper and lower layers with different porosities. Under the premise of ensuring that the capacity remains basically unchanged, a larger liquid retention amount is achieved and the migration rate of lithium ions inside the electrode is increased, thereby greatly improving the fast charging performance. With the help of the porous structure of the second electrode layer, the discharge products generated by the active material during the charge and discharge process can be effectively adsorbed, thereby preventing them from dissolving in the electrolyte. Through the blocking and fixing effect of the porous structure on the discharge products, most of the polysulfides soluble in the electrolyte can be confined in the conductive network of the positive electrode sheet, and the "shuttle effect" caused by the soluble polysulfides in the electrolyte shuttling back and forth between the positive and negative electrodes during the cycle process can be fully suppressed. Some polysulfides adsorbed in the conductive network of the porous carbon layer can participate in the electrochemical reaction again during the charge and discharge process, reducing the irreversible capacity of the active sulfur and improving the utilization rate of sulfur. The pores left after the pore-forming agent is heated and decomposed can well adapt to the volume expansion of copper sulfide nanoparticles during charge and discharge, thereby improving the stability of the material structure, thereby achieving the effect of stabilizing the electrode structure of the positive electrode sheet and enabling the good electrochemical properties of the composite material to be fully realized. At the same time, the multilayer electrode of the present application includes at least a first electrode layer and a second electrode layer with a porous structure. Different mass portions of the pore-forming agent ammonium bicarbonate are added to the second slurry. The porosity of the second electrode layer farther away from the current collector is larger, so that the surface of the electrode has a rich pore structure. These pores are conducive to the full infiltration of the electrolyte, can accommodate sufficient electrolyte, and improve the cycle performance of the battery. DETAILED DESCRIPTION

[0015] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Example 1 The preparation method of the positive electrode active material comprises the following steps: 5 mmol of copper sulfate pentahydrate and 6 mg of polyvinyl pyrrolidone were added to 60 mL of water and dissolved, and then 10 mmol of sodium thiosulfate pentahydrate was dissolved in 20 mL of water. The above two solutions were mixed evenly and transferred into a 100 mL polytetrafluoroethylene reactor, which was sealed and kept at 180°C for 5 h. The supernatant was poured off, and the mixture was washed with deionized water and centrifuged for 3 times. Finally, the mixture was dried in a 45°C oven to obtain black copper sulfide nanoparticles. Add 0.5 mL of titanium isopropoxide and 8 mL of pinene alcohol to 0.2 g of ethyl cellulose, stir until completely dissolved, put into an agate mortar, then add 0.4 g of copper sulfide nanoparticles and 0.4 g of hydroxyl multi-walled carbon nanotubes to the agate mortar, and grind thoroughly for 2 h until no obvious particles are present to obtain a carbon nanotube-copper sulfide composite material as a positive electrode active material.

[0017] The method for preparing the multilayer electrode comprises the following steps: Preparation of positive electrode sheet: The positive electrode active material, conductive carbon black and polyvinylidene fluoride obtained above were dissolved in N-methylpyrrolidone at a mass ratio of 96:2:2 and mixed evenly to prepare a positive electrode first slurry, 1 mass part, 2 mass parts and 3 mass parts of pore-forming agent ammonium bicarbonate were added to the above positive electrode first slurry respectively, and continued to stir and disperse evenly to obtain a series of positive electrode second slurries with different pore-forming agent contents; then the positive electrode first slurry was evenly coated on the positive electrode current collector aluminum foil, and then a 1 mass part of ammonium bicarbonate was coated on the positive electrode first slurry. The positive electrode second slurry is prepared, the positive electrode first slurry and the positive electrode second slurry are alternately coated, the farther away from the current collector the second slurry is, the higher the content of the pore-forming agent is, and then dried at 85°C, cold pressed, trimmed, cut, slit, and welded to the pole ears to prepare the positive electrode sheet; wherein the positive electrode first slurry and the positive electrode second slurry are coated 3 times, and the coating amount each time is the same, the thickness of the positive electrode first electrode layer obtained by coating the positive electrode first slurry is 55μm, and the thickness of the positive electrode second electrode layer obtained by coating the positive electrode second slurry is 60μm.

[0018] Preparation of negative electrode sheet: Graphite, conductive carbon black, styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose are dissolved in deionized water at a mass ratio of 92:2:5:1 and mixed evenly to form a first negative electrode slurry, 1, 2, and 3 parts by mass of pore-forming agent ammonium bicarbonate are added to the first negative electrode slurry, respectively, and stirred and dispersed evenly to obtain a series of second negative electrode slurries with different pore-forming agent contents; then, the first negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and then a 1 part by mass ammonium bicarbonate is coated on the first negative electrode slurry. The negative electrode second slurry of ammonium hydrogen, the negative electrode first slurry and the negative electrode second slurry are alternately coated, and the farther away from the current collector, the higher the content of the pore-forming agent in the second slurry is coated, and then dried at 85°C and cold pressed, and then trimmed, cut, stripped, and welded to the pole ears to prepare the negative electrode sheet; wherein the negative electrode first slurry and the negative electrode second slurry are coated 3 times, the thickness of the positive electrode first electrode layer obtained by coating the positive electrode first slurry is 55μm, and the thickness of the positive electrode second electrode layer obtained by coating the positive electrode second slurry is 60μm.

[0019] The preparation method of a lithium-ion battery comprises the following steps: The positive electrode sheet, negative electrode sheet and isolation membrane (polypropylene microporous membrane with a thickness of 12μm) are made into a battery cell through a winding process, and then packaged with an aluminum-plastic film and injected with electrolyte. The electrolyte uses 1M lithium hexafluorophosphate as the lithium salt, and the organic solvent uses ethylene carbonate / ethyl methyl carbonate = 3:7 (volume ratio). After the formation, capacity, shaping and other processes, the preparation of the lithium-ion battery is completed.

[0020] Example 2 The method for preparing the positive electrode active material comprises the following steps: 5 mmol of copper sulfate pentahydrate and 6 mg of polyvinyl pyrrolidone were added to 60 mL of water and dissolved, and then 10 mmol of sodium thiosulfate pentahydrate was dissolved in 20 mL of water. The above two solutions were mixed evenly and transferred into a 100 mL polytetrafluoroethylene reactor, which was sealed and kept at 180°C for 5 h. The supernatant was poured off, and the mixture was washed with deionized water and centrifuged for 3 times. Finally, the mixture was dried in a 45°C oven to obtain black copper sulfide nanoparticles. 0.6 mL of titanium isopropoxide and 10 mL of pinene alcohol were added to 0.3 g of ethyl cellulose, stirred until completely dissolved, and put into an agate mortar. Then, 0.6 g of copper sulfide nanoparticles and 0.4 g of hydroxyl multi-walled carbon nanotubes were added to the agate mortar, and ground thoroughly for 2 h until no obvious particles were present to obtain a carbon nanotube-copper sulfide composite material as a positive electrode active material.

[0021] The preparation steps of the multilayer electrode and the lithium ion battery are exactly the same as those in Example 1.

[0022] Example 3 The method for preparing the positive electrode active material comprises the following steps: 5 mmol of copper sulfate pentahydrate and 6 mg of polyvinyl pyrrolidone were added to 60 mL of water and dissolved, and then 10 mmol of sodium thiosulfate pentahydrate was dissolved in 20 mL of water. The above two solutions were mixed evenly and transferred into a 100 mL polytetrafluoroethylene reactor, which was sealed and kept at 180°C for 5 h. The supernatant was poured off, and the mixture was washed with deionized water and centrifuged for 3 times. Finally, the mixture was dried in a 45°C oven to obtain black copper sulfide nanoparticles. Add 0.5 mL of titanium isopropoxide and 8 mL of pinene alcohol to 0.2 g of ethyl cellulose, stir until completely dissolved, put into an agate mortar, then add 0.8 g of copper sulfide nanoparticles and 0.4 g of hydroxyl multi-walled carbon nanotubes to the agate mortar, and grind thoroughly for 2 h until no obvious particles are present to obtain a carbon nanotube-copper sulfide composite material as a positive electrode active material.

[0023] The preparation steps of the multilayer electrode and the lithium ion battery are exactly the same as those in Example 1.

[0024] Example 4 The method for preparing a multilayer electrode comprises the following steps: Preparation of positive electrode sheet: The obtained positive electrode active material carbon nanotube-copper sulfide composite material, conductive carbon black and polyvinylidene fluoride are dissolved in N-methylpyrrolidone at a mass ratio of 96:2:2 and mixed evenly to prepare a positive electrode first slurry, 1.5 parts by mass and 3 parts by mass of pore-forming agent ammonium bicarbonate are added to the above positive electrode first slurry respectively, and the mixture is stirred and dispersed evenly to obtain a series of positive electrode second slurries with different pore-forming agent contents; then the positive electrode first slurry is evenly coated on the positive electrode current collector aluminum foil. , then coating the first positive electrode slurry with a second positive electrode slurry containing 1.5 parts by mass of ammonium bicarbonate, then coating the first positive electrode slurry, and finally coating the second positive electrode slurry containing 3 parts by mass of ammonium bicarbonate, followed by drying at 85°C, cold pressing, trimming, cutting, stripping, and welding the pole ears to prepare a positive electrode sheet; wherein the thickness of the positive electrode first electrode layer obtained by coating the first positive electrode slurry is 75 μm, and the thickness of the positive electrode second electrode layer obtained by coating the second positive electrode slurry is 80 μm.

[0025] Preparation of negative electrode sheet: Graphite, conductive carbon black, styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose are dissolved in deionized water at a mass ratio of 92:2:5:1 and mixed evenly to form a first negative electrode slurry, 1.5 parts by mass and 3 parts by mass of pore-forming agent ammonium bicarbonate are added to the first negative electrode slurry, respectively, and stirring and dispersing are continued to be uniform to obtain a series of second negative electrode slurries with different pore-forming agent contents; then the first negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and then the second negative electrode slurry containing 1.5 parts by mass of ammonium bicarbonate is coated on the first negative electrode slurry, followed by the first negative electrode slurry, and finally the second negative electrode slurry containing 3 parts by mass of ammonium bicarbonate is coated, followed by drying at 85°C and cold pressing, and then trimming, cutting, stripping, and welding the pole ears to prepare a negative electrode sheet; wherein, the thickness of the first positive electrode layer obtained by coating the first positive electrode slurry is 75 μm, and the thickness of the second positive electrode layer obtained by coating the second positive electrode slurry is 80 μm.

[0026] The preparation steps of the positive electrode active material and the lithium ion battery are exactly the same as those in Example 1.

[0027] Example 5 The method for preparing a multilayer electrode comprises the following steps: Preparation of positive electrode sheet: The obtained positive electrode active material carbon nanotube-copper sulfide composite material, conductive carbon black and polyvinylidene fluoride are dissolved in N-methylpyrrolidone in a mass ratio of 96:2:2 and mixed evenly to form a first positive electrode slurry, 2.5 parts by mass of pore-forming agent ammonium bicarbonate are added to the above first positive electrode slurry, and stirring and dispersing are continued to be evenly obtained to obtain a second positive electrode slurry; then the first positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then the second positive electrode slurry is coated on the first positive electrode slurry, and then dried at 85°C, cold pressed, trimmed, cut, slit, and welded to the ears to prepare a positive electrode sheet; wherein the first positive electrode slurry and the second positive electrode slurry are coated once, the thickness of the first positive electrode layer obtained by coating the first positive electrode slurry is 150 μm, and the thickness of the second positive electrode layer obtained by coating the second positive electrode slurry is 160 μm.

[0028] Preparation of negative electrode sheet: Graphite, conductive carbon black, styrene-butadiene rubber and thickener sodium carboxymethyl cellulose are dissolved in deionized water in a mass ratio of 92:2:5:1 and mixed evenly to form a first negative electrode slurry, 2.5 parts by mass of pore-forming agent ammonium bicarbonate are added to the first negative electrode slurry, and stirring is continued to disperse evenly to obtain a second negative electrode slurry; then the first negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and then the second negative electrode slurry is coated on the first negative electrode slurry, followed by drying at 85°C and cold pressing, and then trimming, cutting, stripping and welding the pole ears to prepare a negative electrode sheet; wherein the first negative electrode slurry and the second negative electrode slurry are coated once, the thickness of the first positive electrode layer obtained by coating the first positive electrode slurry is 150 μm, and the thickness of the second positive electrode layer obtained by coating the second positive electrode slurry is 160 μm.

[0029] The preparation steps of the positive electrode active material and the lithium ion battery are exactly the same as those in Example 1.

[0030] Comparative Example 1 The preparation of the positive electrode active material was omitted, and copper sulfide was used as the positive electrode active material to prepare a multilayer electrode sheet and a lithium ion battery. The remaining components and preparation steps were completely consistent with those in Example 1.

[0031] Comparative Example 2 The preparation method of the multilayer electrode comprises the following steps: Preparation of positive electrode sheet: The obtained positive electrode active material carbon nanotube-copper sulfide composite material, conductive carbon black and polyvinylidene fluoride are dissolved in N-methylpyrrolidone in a mass ratio of 96:2:2 and mixed evenly, and then 2.5 parts by mass of pore-forming agent ammonium bicarbonate are added, and stirring and dispersion are continued to be evenly prepared to form a positive electrode slurry, and the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried at 85°C, cold pressed, trimmed, cut, stripped, and welded to the pole ears to prepare a positive electrode sheet.

[0032] Preparation of negative electrode sheet: Graphite, conductive carbon black, styrene-butadiene rubber and thickener sodium carboxymethyl cellulose are dissolved in deionized water in a mass ratio of 92:2:5:1 and mixed evenly, and then 2.5 parts by mass of pore-forming agent ammonium bicarbonate are added, and the mixture is stirred and dispersed evenly to form a negative electrode slurry, which is evenly coated on the negative electrode current collector copper foil, and then dried at 85°C and cold pressed, and then trimmed, cut into pieces, slit and welded to the ears to prepare a negative electrode sheet.

[0033] The preparation steps of the positive electrode active material and the lithium ion battery are exactly the same as those in Example 1.

[0034] Comparative Example 3 The preparation method of the multilayer electrode comprises the following steps: Preparation of positive electrode sheets: The obtained positive electrode active material carbon nanotube-copper sulfide composite material, conductive carbon black and polyvinylidene fluoride are dissolved in N-methylpyrrolidone in a mass ratio of 96:2:2 and mixed evenly to prepare positive electrode slurry, and the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil, and then dried at 85°C, cold pressed, trimmed, cut, stripped, and welded to the pole ears to prepare positive electrode sheets.

[0035] Preparation of negative electrode sheets: Graphite, conductive carbon black, styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose are dissolved in deionized water in a mass ratio of 92:2:5:1 and mixed evenly to form a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode collector copper foil, then dried at 85°C and cold pressed. After that, the negative electrode sheets are prepared by trimming, cutting, stripping, and welding the pole ears.

[0036] The preparation steps of the positive electrode active material and the lithium ion battery are exactly the same as those in Example 1.

[0037] Comparative Example 4 The preparation method of the multilayer electrode comprises the following steps: Preparation of positive electrode sheet: The obtained positive electrode active material, conductive carbon black and polyvinylidene fluoride are dissolved in N-methylpyrrolidone in a mass ratio of 96:2:2 and mixed evenly to form a first positive electrode slurry, 2 parts by mass of pore-forming agent ammonium bicarbonate are added to the above first positive electrode slurry, and stirring and dispersing are continued to be evenly performed to obtain a second positive electrode slurry; then the first positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then the second positive electrode slurry is coated on the first positive electrode slurry, and the first positive electrode slurry and the second positive electrode slurry are alternately coated, each coated 3 times, and then dried at 85°C, and then cold pressed, trimmed, cut, slit, and welded to the pole ears to prepare a positive electrode sheet.

[0038] Preparation of negative electrode sheet: Graphite, conductive carbon black, styrene-butadiene rubber and thickener sodium carboxymethyl cellulose are dissolved in deionized water in a mass ratio of 92:2:5:1 and mixed evenly to form a first negative electrode slurry, 2 parts by mass of pore-forming agent ammonium bicarbonate are added to the first negative electrode slurry, and stirring and dispersing are continued to be evenly performed to obtain a second negative electrode slurry; then the first negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and then the second negative electrode slurry is coated on the first negative electrode slurry, the first negative electrode slurry and the second negative electrode slurry are coated alternately, each coated 3 times, and then dried at 85°C and cold pressed, and then trimmed, cut into pieces, slit, and welded to the pole ears to prepare a negative electrode sheet.

[0039] The preparation steps of the positive electrode active material and the lithium ion battery are exactly the same as those in Example 1.

[0040] Electrochemical performance testing: The LAND battery test system was used to test the electrochemical performance of the batteries prepared by the multilayer electrodes prepared by the preparation methods of Examples 1-5 and Comparative Examples 1-4. The voltage test range was 0.01-3.0V and the test temperature was 25°C. The test results are shown in the following table:

[0041] It can be seen from the data in the above table that the lithium ion battery prepared by the multilayer electrode obtained by the preparation method of Examples 1-5 of the present invention has high first reversible specific capacity and first coulomb efficiency, and has excellent capacity performance, rate performance and cycle performance. In Comparative Example 1, copper sulfide is used as the positive electrode active material to prepare the multilayer electrode and battery, and in Comparative Example 2, a pore former is added to the slurry to prepare a single-layer electrode. In Comparative Example 4, the content of the pore former in the second slurry is the same, and the measured capacity performance, rate performance and cycle performance are all reduced, and in Comparative Example 3, no pore former is added to prepare the single-layer electrode, and the measured capacity performance, rate performance and cycle performance are significantly reduced, indicating that the composite of carbon nanotubes and copper sulfide nanoparticles as the positive electrode active material of the battery, and the preparation of multilayer electrodes by adding different contents of pore formers in the electrode slurry can effectively improve the capacity performance, rate performance and cycle performance of lithium ion batteries.

[0042] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a multilayer electrode, characterized in that: At least the following steps are included: Mixing the active material, the conductive agent and the binder to obtain a first slurry; Adding a pore-forming agent into the first slurry and mixing the mixture to obtain a second slurry; Applying the first slurry on the current collector to form a first electrode layer; coating the second slurry on the first electrode layer to form a second electrode layer; The first slurry and the second slurry are alternately coated and dried to form a multilayer electrode; The multilayer electrode comprises at least one of the first electrode layer and one of the second electrode layer, the active material is a positive electrode active material or a negative electrode active material, the positive electrode active material is a carbon nanotube-copper sulfide composite material, and the second electrode layer is a porous structure.

2. A method for preparing a multilayer electrode according to claim 1, characterized in that: The porosity of the second electrode layer far from the current collector is greater than the porosity of the second electrode layer close to the current collector.

3. A method for preparing a multilayer electrode according to claim 1, characterized in that: The preparation of the positive electrode active material comprises at least the following steps: Add ethyl cellulose to titanium isopropoxide and terpineol and stir until completely dissolved, then place in an agate mortar; Then, copper sulfide nanoparticles and hydroxyl multi-walled carbon nanotubes are added and fully ground until no obvious particles are present to obtain a positive electrode active material; Wherein, the mass ratio of the hydroxyl multi-walled carbon nanotubes to the nano copper sulfide is 1:2-4.

4. A method for preparing a multilayer electrode according to claim 3, characterized in that: The method for preparing the copper sulfide nanoparticles comprises at least the following steps: copper sulfate pentahydrate and polyvinyl pyrrolidone are added into water and dissolved to obtain solution A; Dissolve sodium thiosulfate pentahydrate in water to obtain solution B; The solution A and the solution B are mixed evenly and then transferred into a reaction kettle and sealed, reacted at 160-180°C for 4-6 hours, cooled to room temperature, washed and centrifuged, and placed in an oven for drying to obtain copper sulfide nanoparticles; Wherein, the particle size of the copper sulfide nanoparticles is 150-500nm.

5. The method for preparing a multilayer electrode according to claim 1, characterized in that: The pore-forming agent is ammonium bicarbonate, and the added amount of the pore-forming agent accounts for 0.1-5% of the mass of the second slurry.

6. A method for preparing a multilayer electrode according to claim 1, characterized in that: The preparation temperature of the second slurry is less than or equal to 30°C, and the drying temperature is greater than or equal to 70°C.

7. The method for preparing a multilayer electrode according to claim 1, characterized in that: The surface density of the first slurry accounts for 20% to 80% of the overall surface density, the surface density of the second slurry accounts for 20% to 80% of the overall surface density, and the sum of the first slurry and the second slurry is the overall surface density.

8. A method for preparing a multilayer electrode according to claim 1, characterized in that: The thickness of the first electrode layer is at least 12 μm, the thickness of the second electrode layer is at least 10 μm, and the thickness of the first electrode layer and the second electrode layer is 300-500 μm.

9. The method for preparing a multilayer electrode according to claim 1, characterized in that: The negative electrode active material includes at least one of natural graphite or artificial graphite, the conductive agent includes at least one of self-conductive carbon black, acetylene black, carbon nanotubes or graphene, and the binder includes at least one of ethyl cellulose, titanium isopropoxide, terpineol, polyvinylidene fluoride, hexafluoropropylene, hydrogenated nitrile rubber or styrene butadiene rubber.